2011
DOI: 10.1021/jp201565z
|View full text |Cite
|
Sign up to set email alerts
|

Graphite-Shelled Si Nanoparticles and Their Au/Si Heterodimers: Preparation, Photoluminescence, and Second Harmonic Generation

Abstract: ARTICLEstructures. The fluorescence enhancement and featured strong SHG signal raise potential applications for graphite-shelled Si QDs as cell biolabeling agents and contrast agents in deep tissue microscopy and noninvasive optical tomography.' ASSOCIATED CONTENT b S Supporting Information. Table S1 (correction of CIE chromaticity coordinates x and y with varying ratios of Si@C QDs and Rhodamine 610) and Figures S1ÀS4 (TEM images and size histograms, XRD measurements and Raman spectra, and EDS analysis). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…It is worth mentioning that such graphitic shells are formed on NPs synthesized using metal targets in certain organic liquids such as toluene [36,40] and dimethyl sulfoxide (DMSO). [42] Interestingly, such shell formation is absent in ZnO and CdS NPs synthesized using ZnO [43] and CdS [44] targets. [41] It is reported that the aromatic debris from these solvents acts as a carbon source for graphitization of carbon which leads to the shell formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning that such graphitic shells are formed on NPs synthesized using metal targets in certain organic liquids such as toluene [36,40] and dimethyl sulfoxide (DMSO). [42] Interestingly, such shell formation is absent in ZnO and CdS NPs synthesized using ZnO [43] and CdS [44] targets. [41] It is reported that the aromatic debris from these solvents acts as a carbon source for graphitization of carbon which leads to the shell formation.…”
Section: Resultsmentioning
confidence: 99%
“…[41] It is reported that the aromatic debris from these solvents acts as a carbon source for graphitization of carbon which leads to the shell formation. [42] Interestingly, such shell formation is absent in ZnO and CdS NPs synthesized using ZnO [43] and CdS [44] targets. Therefore, several factors influence the formation of graphitic shells on the synthesized NPs in liquid using LAL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Recently, it has been reported that the synthesis of nanomaterials in organic solvents can inuence the composition and structure of the products. [22][23][24][25] In the present work we report a new luminescent hybrid nanomaterial, which is produced by the pulsed laser ablation of an inorganic solid target in an organic (hydrocarbon) liquid. The material is fabricated in the form of spherical nanoparticles (NPs) with a core-shell structure, where the inorganic core is produced by the laser ablation of the target material, whereas the luminescent shell is a carbon structure (such as multilayer graphite or amorphous carbon), which is formed on the inorganic core surface due to the thermal decomposition of the hydrocarbon liquid that is in contact with the hot core nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…In the range of visible light, the absorptions for all Si samples become weak and comparable at the tails, implying inhomogeneous distribution of the sizes in all Si nanopowders. 38 The direct band gaps (E d ) were obtained by linear extrapolation to zero in the plots of (ahn) 2 versus photon energy (Fig. 7b), these are 2.89, 2.92, and 3.02 eV for Si NPs, NSs, and NRs, respectively.…”
mentioning
confidence: 99%